Discernment and biblical spirituality: an overview and evaluation of recent research - Kees Waaijman (Acta Theologica)
This article briefly and very generally explores some of the developments in the field of biblical spirituality over the past six decades by analysing and discussing some seminal publications on the theme of discernment. It begins the overview with the articles on discernment and discretion in the Dictionnaire de Spiritualité (1957) and then focuses on publications of the past twenty years. It discusses how discernment has moved beyond uncritically assumed dichotomies, beyond the separation of discernment and discretion, and the division between the Bible and philosophy. It also points out how recent publications emphasised for the first time the importance of communal discernment and thus overcame the untenable dualism between personal and communal discernment.